Contribution of calcium in drinking water from a South American country to dietary calcium intake - Cormick, Gabriela (2020)
Objective: To describe the calcium concentration of tap and bottled waters from Argentina and to estimate the contribution of drinking water to calcium recommendations. Results: Calcium concentrations provided by water authorities ranged from 6 to 105 mg/L. The mean calcium level of samples analysed at the Laboratorio de Ingeniería Sanitaria, National University of La Plata was 15.8 (SD ± 13.2) mg/L and at the Bone Biology Laboratory of the National University of Rosario was 13.1 (± 10.0) mg/L. Calcium values of samples from supply systems and private wells was similar. Most bottled waters had calcium levels well below 50 mg/L. The intake of one litre of drinking water from Argentina could represent in average between 1.2 and 8.0% of the calcium daily values for an adult.